HISTORICAL, CULTURAL, AND LINGUISTIC IMPORTANCE OF REMEMBRANCES (ZIKR-E-MIR). - Shankar, Biklendu; Bharaty, Samaresh; Ranjan, Ashish (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Zikr-e-Mir is considered an autobiographical text of the Mir Muhammad Taqi. Mir indicates his claim to be a descendant of the prophet Muhammad; he is also regarded as the important Urdu poet of the 18th century and considered the most influential ghazal poet of north India. Mir wrote Nikat-al-Shu’ara’, Faize-e-Mir, and Zikr-e-Mir during his life. But we will limit our discussion only to Zikr-e-Mir. With its help, we can trace the text's historical, cultural, and linguistic importance. If we look at the text carefully, it contains a brief notice of Mir’s ancestors, a short section on Muhammad Ali, his friend Amanullah, and political events of Mir’s time that he witnessed.